Kinerja Simpang Tak Bersinyal dan Hambatan Samping selama Ramadan di Kawasan Perkotaan - Yoga Kaharudin Bahri; Galuh Pramita; Lilik Ariyanto (Jurnal Konstruksi, 2025)
This study analyzes the performance of two unsignalized intersections in Bandar Lampung during Ramadan, namely the intersection of Jalan Imam Bonjol–Pagar Alam and Jalan Imam Bonjol–Sisingamangaraja. Data was obtained through a field survey conducted over three days during rush hour and analyzed using the 2014 PKJI method. The results show that the highest degree of saturation (DJ) occurred at the Sisingamangaraja intersection (DJ=0.9490) with LOS E, and the highest side obstacle of 60.1. The dominant obstacles came from stopped vehicles and pedestrians, especially in the afternoon before breaking the fast. These findings confirm the need for adaptive traffic management during Ramadan at unsignalized intersections in commercial areas.